Anti-Müllerian hormone (AMH) in the Diagnosis of Menstrual Disturbance Due to Polycystic Ovarian Syndrome - Abbara, Ali; Eng, Pei Chia; Phylactou, Maria; Clarke, Sophie A.; Hunjan, Tia; Roberts, Rachel; Vimalesvaran, Sunitha; Christopoulos, George; Islam, Rumana; Purugganan, Kate; Comninos, Alexander N.; Trew, Geoffrey H.; et al. (Frontiers in Endocrinology, 2019)
Introduction: Polycystic ovarian syndrome (PCOS) is a leading cause of female subfertility worldwide, however due to the heterogeneity of the disorder, the criteria for diagnosis remains subject to conjecture. In the present study, we evaluate the utility of serum anti-Müllerian hormone (AMH) in the diagnosis of menstrual disturbance due to PCOS. Method: Menstrual cycle length, serum AMH, gonadotropin and sex-hormone levels, total antral follicle count (AFC), body mass index (BMI) and ovarian morphology on ultrasound were analyzed in a cohort of 187 non-obese women, aged 18-35years, screened for participation in a clinical trial of fertility treatment between 2013 and 2016 at a tertiary reproductive endocrine center. Results: Serum AMH was higher in women with menstrual disturbance when compared to those with regular cycles (65.6 vs 34.8 pmol/L; P<0.0001). The odds of menstrual disturbance was increased 28.5-fold (95% CI 3.6-227.3) in women with serum AMH >60 pmol/L, in comparison to those with an AMH <15 pmol/L. AMH better discriminated women with menstrual disturbance (area under ROC 0.77) from those with regular menstrual cycles than AFC (area under ROC 0.67), however the combination of the two markers increased discrimination than either measure alone (0.83; 95% CI 0.77-0.89). Serum AMH was higher in women with all three features of PCOS (menstrual disturbance, hyperandrogenism, polycystic ovarian morphology) when compared to women with none of these features (65.6 pmol/L vs 14.6 pmol/L; P<0.0001). The odds of menstrual disturbance were increased by 10.7-fold (95% CI 2.4-47.1) in women with bilateral polycystic morphology ovaries than those with normal ovarian morphology. BMI was a stronger predictor of free androgen index (FAI) than either AMH or AFC. Conclusion: Serum AMH could serve as a useful biomarker to indicate the risk of menstrual disturbance due to PCOS. Women with higher AMH levels had increased rates of menstrual disturbance and an increased number of symptoms of PCOS.